PENGEMBANGAN MEDIA LAYANAN MASYARAKAT PENANGGULANGAN DAN PEMANFAATAN SAMPAH BERBASIS MULTIMEDIA MENGGUNAKAN METODE MDLC - Arif Muhamad Ramdani (PROCEEDING STIMA)
It has long been a serious problem in the community, this is because it has become a culture when the existing waste is thrown away, whether organic or inorganic waste. Whereas if people can use it well, the waste can provide more value and even the selling value for Majalengka community. Multimedia-based visualization is one of the methods used as a community service that helps the DLH party in providing information to the community about the prevention and utilization of waste into useful goods for the community itself. In this study, the authors use Adobe Flash Professional CS6 application to create a multimedia-based visualization with MDLC (Multimedia Development Life Cycle) method. This visualization contains how to utilize organic waste into compost and biogas, and inorganic waste for handicrafts and in addition can also be recycled back into plastic. With this visualization as a public service media is expected Majalengka community can be more concerned about the environment. In addition, the community also has knowledge how to overcome the organic and inorganic waste in order to be used as a product that has a sale value.